The Correlation Between English Classroom Environment and Learning Motivation on EFL Secondary School Students - Anisah, Siti; Syahid, Abdul; Mirza, Akhmad Ali (Universitas Pahlawan Tuanku Tambusai, 2025)
The classroom environment plays a crucial role in supporting students' learning motivation. A comfortable environment can enhance focus, engagement, and academic achievement, while poor conditions may hinder students' motivation to learn. Therefore, this study aims to analyze the correlation between the English classroom environment and students' learning motivation at the secondary school level using a quantitative correlational method. Data were collected from 67 students at a Madrasah Tsanawiyah in Palangka Raya, Central Kalimantan, through questionnaires on classroom environment and learning motivation. Spearman’s correlation analysis showed a significant positive correlation (rho = 0.405, p 0.001), indicating that a well-maintained classroom environment can enhance students’ learning motivation. Key factors such as sound insulation, lighting, temperature, ventilation, and classroom decoration influence students’ learning experiences. A comfortable and supportive classroom helps improve students’ focus and engagement, while an inadequate environment may reduce their motivation. These findings highlight the importance of optimizing the classroom environment to enhance students' motivation. Teachers can improve classroom management by arranging flexible seating, ensuring proper lighting, and maintaining good air circulation. Additionally, policymakers should consider upgrading school facilities to create a more conducive learning environment that fosters student motivation. With a better classroom environment, students can stay more focused, motivated, and achieve better academic outcomes.